Institutional firesetting in a forensic inpatient population - Willmot, Phil (The journal of forensic psychiatry & psychology, 2023)
Institutional firesetting is a widespread and serious problem in custodial settings. However, there is very little research into the subject. This paper describes the characteristics and firesetting histories of 32 patients with histories of institutional firesetting in a secure psychiatric unit in the UK. Only six patients (18.8%) had a prior conviction for firesetting, while a further eight (25.0%) had a history of firesetting but no conviction). All institutional firesetting was carried out alone, most commonly in a cell or bedroom. Institutional firesetting was significantly more common among patients with a diagnosis of personality disorder than among those with a diagnosis of mental illness.The results are consistent with the M-TTAF trajectories model of firesetting. Different patterns of firesetting may emerge in institutional settings because firesetting may be one of an extremely limited repertoire of problem solving strategies and may be inadvertently reinforced in these settings. These results suggest that there may be a subgroup of institutional firesetters with no previous history of firesetting and this is a group that merits more detailed study.